Pelatihan Kompetensi Kewirausahaan dan Digital Marketing guna Mengoptimalkan Penjualan Produk UMKM di Desa Wisata Jipangan - Ginanjar Setyo Nugroho; Murniady Muchran (Jurnal Pengabdian UNDIKMA, 2023)
This service aims to improve the competencies in order to optimize sales of MSME products. The method of this service is participatory training. The partner of this service is several MSME owners in Jipangan Tourism Village, Bangunjiwo, Kasihan, Bantul, Special Region of Yogyakarta. The activity evaluation instrument uses a pre-test and post-test, which is then analyzed descriptively. The results of this service show that there is an increase in MSME owners’ knowledge related to entrepreneurship by 70% and knowledge related to digital marketing by 37,5%. In addition, MSMEs have the motivation to keep trying to develop their products with innovative patterns in creating more significant opportunities by maximizing marketing through the use of social media.